Sarcopenia: pathogenesis and diagnosis - I. I. Grigorieva; T. A. Raskina; M. V. Letaeva; O. S. Malyshenko; Yu. V. Averkieva; V. L. Masenko; A. N. Kokov (Фундаментальная и клиническая медицина, 2019)
Increase in life expectancy is among the most significant achievements of modern medicine. Currently, the majority of patients are elderly, being characterised by multimorbidity and frailty. Sarcopenia, a progressive and generalized loss of skeletal muscle mass and strength, is associated with a reduced quality of life and high risk of adverse outcomes including disability and death in these patients. Age-related neuromuscular degeneration, decline of circulating anabolic hormones, chronic inflammation and oxidative stress considerably affect the development of sarcopenia. In addition, low intake of proteins and carbohydrates along with a decrease in physical activity also affect muscular homeostasis. Being combined with obesity, osteopenia/osteoporosis, and vitamin D deficiency, sarcopenia worsens the prognosis of the patient in terms of life expectancy. In this review, we discuss the current advances in epidemiology, pathophysiology, and diagnosis of sarcopenia.